Genomic variation reveals demographic history and biological adaptation of the ancient relictual, lotus (Nelumbo Adans.). Issue 1 (19th February 2022) - Zheng, Xingwen; Wang, Tao; Cheng, Teng; Zhao, Lingling; Zheng, Xingfei; Zhu, Fenglin; Dong, Chen; Xu, Jinxing; Xie, Keqiang; Hu, Zhongli; Yang, Liangbo; Diao, Ying
Abstract: Lotus ( Nelumbo Adans.), a relict plant, is testimony to long-term sustained ecological success, but the underlying genetic changes related to its survival strategy remain unclear. Here, we assembled the high-quality lotus genome, investigated genome variation of lotus mutation accumulation (MA) lines and reconstructed the demographic history of wild Asian lotus. We identified and validated 43 base substitutions fixed in MA lines, implying a spontaneous mutation rate of 1.4 × 10 −9 bases/generation in lotus shoot stem cells. The past history of the lotus revealed that the ancestors of the lotus in eastern and southern Asia could be traced back to 20 million years ago and twice experienced significant bottlenecks and population splits. We further identified selected genes among three lotus groups in different habitats, suggesting that 453 differed genes between the tropical and temperate group and 410 differed genes between two subgroups from Northeastern China and the Yangtze River–Yellow River Basin might play important roles in natural selection in the lotus's adaptation and resilience. Our findings not only improve understanding of the evolutionary history of the lotus and the genetic basis of its survival advantages, but also provide valuable data for addressing various questions in evolution and protection for relict plants.